Formation of Hollow Gold Nanocrystals by Nanosecond Laser Irradiation - (:unkn) unknown (American Chemical Society, 2020)
The irradiation of spherical gold nanoparticles (AuNPs) with nanosecond laser pulses induces shape transformations yielding nanocrystals with an inner cavity. The concentration of the stabilizing surfactant, the use of moderate pulse fluences, and the size of the irradiated AuNPs determine the efficiency of the process and the nature of the void. Hollow-nanocrystals are obtained when molecules from the surrounding medium (e.g., water and organic matter derived from the surfactant) are trapped during laser pulse irradiation. These experimental observations suggest the existence of a subtle balance between the heating and cooling processes experienced by the nanocrystals, which induce their expansion and subsequent recrystallization keeping exogenous matter inside. The described approach provides valuable insight into the mechanism of interaction of a pulsed nanosecond laser with AuNPs, along with interesting prospects for the development of hollow plasmonic nanoparticles with potential applications related to gas and liquid storage at the nanoscale.